Congenital Kaposiform Hemangioendothelioma with Kasabach–Merritt Phenomenon Successfully Treated with Low‐Dose Radiation Therapy. Issue 5 (5th March 2013) - Malhotra, Yogangi; Yang, Catherine S.; McNamara, Joseph; Antaya, Richard J.
Abstract Kaposiform hemangioendothelioma (KHE) associated with Kasabach–Merritt phenomenon is a life‐threatening vasculopathy. The current mainstay treatment for KHEs is corticosteroids and chemotherapy, but these medications do not work for all patients and carry significant side effects. We report a neonate with a large congenital KHE who responded extremely well to low‐dose radiation therapy.